Síntese e caracterização de precursores do tipo hidrotalcita e suas aplicações na reação de reforma a vapor do ácido acético - Borges, Rafael Pacheco (2015)
Among the various existing methodologies for the production of hydrogen as an alternative energy, the use of biomass is a great alternative for this purpose. The processing of biomass by thermochemical technologies such as pyrolysis generates fumes that come from the decomposition of the raw material, exposed to high process temperatures. Subsequently, these vapors condense giving rise to bio-oil, which is a dark liquid composed mainly by organic oxygenated molecules. The bio-oil can be divided into a hydrophobic part (oil itself), which has several applications in industry, and a hydrophilic part that has a low added value due to their lack of utility, as its mainly composition is only water and some carboxylic acids. Thus, it would be interesting to use the aqueous fraction of bio-oil as a raw material in reforming reactions to produce hydrogen, but due to the wide variety of compounds in its constitution, the reaction study becomes complex. One possible solution to this problem is the use of model compounds, such as acetic acid. To perform acetic acid reforming reaction the use of catalysts with high catalytic activity, high selectivity to the desired product and low cost, is required. Therefore, the nickel-based catalysts emerge as a good alternative and among them hydrotalcite precursors are a good choice, mostly because they can generate uniform mixed oxides with a large surface area. This work used precursors of the hydrotalcite type aiming the production of hydrogen using a model compound of the aqueous fraction of bio-oil. For this purpose, five different precursor Mg-Al-Ni, varying their molar ratio Ni / Mg in 0.2, 0.3, 0.4, 0.5, and 0.6 were prepared (02NiMg, 03NiMg, 04NiMg, 05NiMg and 06NiMg). The characterization tests X-ray difraction (XRD), temperature-programmed reduction (TPR), X-ray diffraction in situ (XRD in situ), X-ray absortion near-edge structure (XANES) and temperature-programmed surface reaction (TPSR) were conducted to assess the behavior of each catalyst. It was observed that the compounds and oxides generated from them were successfully synthesized and that the mass content of nickel and magnesium had a direct influence on the reduction time and temperature of each sample. It is possible that the formation of a solid solution (Ni, Mg)O has also influenced on the reducibility of the samples. The minimum temperature required to start the reform reaction or the decomposition reaction of acetic acid was 400 ° C, because at lower temperatures it was not observed the formation of any product. In general, all samples have proved themselves quite stable, as they stood reduced and active throughout the period of analysis of reactions.